Federal unemployment reinsurance and local labor-market policies - Marek Ignaszak; Philip Jung; Keith Küster (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Consider a union of atomistic member states, each faced with idiosyncratic business-cycle shocks. Private cross-border risk-sharing is limited, giving a role to a federal unemployment-based transfer scheme. Member states control local labor-market policies, giving rise to a trade-off between moral hazard and insurance. Calibrating the economy to a stylized European Monetary Union, we find notable welfare gains if the federal scheme's payouts take the member states' past unemployment level as a reference point. Member states' control over policies other than unemployment benefits can limit generosity during the transition phase.
Keywords: E32; E24; E62; 330; Unemployment reinsurance; labor-market policy; fiscal federalism; search and matching